An assessment of heavy metals in poultry chicken giblets using ICP-MS / Nwokoma Oliver Chijioke - Nwokoma Oliver , Chijioke (2017)
Heavy metals concentrations in chicken giblets were assessed to determine their potential toxic level and impact to the inhabitants of Selangor and Kuala Lumpur via consumption of chicken giblets. The concentration of 14 heavy metals such as; Fe, Cu, Mg, Zn, Al, Hg, Sb, As, Pb, Se, Ni, Sr, Cr and Sb were determined in 280 samples of poultry chicken giblets; liver, gizzard and heart samples that were collected from different local markets of Selangor and Kuala Lumpur, Malaysia. The analysis was performed using the Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) and the obtained results were compared with the permissible limits set by World Health Organization (WHO) and The Australia Total Dietary Survey (ATDS). The result shows that all liver samples contain all toxic metals with EDI concentration in (?g/kg) as Al (0.22), Cr (0.00508), As (0.00202), Se (0.00475), and Zn (0.4605), Cd (0.00204), Hg (0.03297), Pb (0.00187), Cu (0.047), and Sb (0.5187) followed by heart with values of Al (0.19037), Cr (0.01725), Se (0.00414), Zn (0.620), Cd (0.01659), Hg (0.014658), Pb (0.0472), Cu (0.06476) and Sb (0.69076) with no As detected. The gizzard samples show no traces of Pb and Cd. However, the heart were found to have the highest average concentration of Sb as 0.371±0.150 ?g/g and followed by the Zn 0.3340±0.06 ?g/g in the same sample. The estimated daily intake (EDI) of antimony as 0.690 ?g/kg in heart and 0.518 ?g/kg in liver samples respectively represents a concern worthy of regular monitoring within the study region.